CIVIL LIABILITY OF DOCTORS DUE TO PROFESSIONAL (MEDICAL) ERROR - Marković, Velisav I (Halo 194 Scientific Journal of Emergency Medicine, 2021)
Civil liability of health care workers and health care institutions is one of the most significant problems in health and medical law. The questions of the real bases of responsibility are always open: medical errors, patient information and guilt in the organization of work. In order to eliminate doubts in practice, the author presents what is considered the concept of professional (medical) error, general conditions of responsibility of the doctor (doctor's guilt, damage to the patient and the cause-and-effect relationship between medical error and damage dealt) as well as the precise explanation of which party has the burden of proof in possible court proceedings.
Keywords: professional error, medical error, civil liability, health care worker